SARS-CoV-2 IgG and IgM Analysis in Patients Who Attended a University Hospital During the COVID-19 Epidemic in Iran - Fayaz , Fariba; Rommasi, Foad; Atefmehr , Leila; Nasiri , Mohammad Javad (Novelty in Biomedicine, 2022)
Background: The world is facing a new coronavirus that causes a respiratory infection called COVID-19. Therefore, there is an increasing request for antibody tests in recovered individuals since they want to evaluate their immunity against SARS-CoV-2 reinfection. Materials and Methods: In our study, we had 1000 blood samples from patients admitted to the Ghiassi Hospital, Tehran, Iran, or were asked to perform serological SARS-COV-2 IgM and IgG tests by their physicians were collected. The antibody levels were assessed via the ELISA assay method using S and N antigens during various waves of the COVID-19 epidemic in Iran. Results: The highest IgG level (2.77) compared to the average (with 95% confidence) is observed in patients infected in the third wave, which is confirmed by the ANOVA test. The mean IgM concentration in the second wave was equal to 0.77 and more than the IgM level in the third wave and the beginning of the fourth wave, which was confirmed by the ANOVA test. Conclusion: Detection of SARS-COV-2 IgG, IgM has significant potential for evaluating the severity and prognosis of COVID-19. In addition, all seroepidemiology data in each community can help Health Commissions for controlling this pandemic. These data also can be used for epidemiological modeling and assessing the prevalence of COVID-19 immunity in society.